MSMEs Competitiveness In Eastern Java: The Role of Innovation and Information Systems Within Organizational Culture - Hofifatul Musyarrofah Efendi; Abdul Qodir; Pardiman (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the effect of organizational culture on performance through the mediating roles of innovation capability and management information systems among Micro, Small, and Medium Enterprises (MSMEs) in the eastern region of Java. The research employs a quantitative approach using a partial least squares structural equation modeling (PLS-SEM) technique. Data were collected through questionnaires distributed to 98 MSME owners and managers. The results indicate that organizational culture has a positive and significant influence on innovation capability and management information systems, both of which, in turn, significantly affect performance. Furthermore, innovation capability and management information systems partially mediate the relationship between organizational culture and performance. These findings suggest that fostering a strong organizational culture can enhance MSME performance when supported by innovative capabilities and effective information management systems. The study contributes to empirical evidence in strategic management and organizational behavior, particularly in the MSME context in eastern Java.